Multifuncionalidad de servicios ecosistémicos en áreas de restauración ecológica del bosque siempreverde piemontano del Sur del Ecuador - Peláez Chimbo, Diego Fernando (2023)
In the Southern Region of Ecuador, the evergreen piedmont forests are not only characterized by high plant diversity but are also crucial for providing multiple ecosystem services (ES) for the benefit of society, a concept known as multifunctionality (M). Nevertheless, human activities have led to the extensive deforestation of these forests for the establishment of productive systems such as agriculture and livestock farming. To restore these degraded areas, both passive and active ecological restoration strategies have been implemented with the aim of recovering ES provision and its multifunctionality. To analyze how these strategies have contributed to the recovery of ES and multifunctionality, we estimated the provision of ES in passive restoration areas (PR), active restoration areas (AR), and mature forests (MF). Based on these estimations, we assessed multifunctionality. For this purpose, nine randomly located 50 × 50 m plots were established in PR, AR, and MF areas. We estimated the potential wood volume provision (WVP) using basal area, total tree height, and a shape factor of 0.7. Non-timber forest products (NTFPs) were determined through secondary information review. To estimate above-ground carbon (AGC), we used the allometric equation for tropical forests, which incorporates tree diameter and total height, wood density by species, and a conversion factor of 0.47. To determine soil carbon (SC), nitrogen (N), phosphorus (P), and potassium (K) values, soil samples were collected at a depth of 30 cm and sent to the laboratory of the Instituto Nacional de Investigaciones Agropecuarias (INIAP) for analysis. Plant diversity, including species richness (R), was determined by the number of species, and diversity (H) was assessed using the Shannon-Wiener index. The multifunctionality indicator was estimated using the average multifunctional approach. The results showed no statistically significant differences between AR and PR in providing WVP, NTFPs, AGC, SC, N, P, K, H, and M, except for R. However, despite the lack of differences, AR areas exhibited greater recovery of plant diversity, NTFPs, SC, N, P, K, and M. In contrast, PR areas predominantly recovered WVP and AGC. As a conclusion, both restoration strategies are important for the recovery of ES multifunctionality in degraded areas and can complement each other, but it should be noted that AR may be much more costly than PR.